Analysis Of Potential Hazards And Risk Assessment Using The Hirarc (Hazard Identification Risk Assessment And Risk Control) Method As An Effort To Prevent Work Accidents At Pt Tunas Ridean Tbk Serang - Salam, Rizky Sabili; Ikhsanudin, Ikhsanudin; Susanto, Eko (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
PT Tunas Ridean TBK is a vehicle provider company throughout Indonesia, as well as part of a subsidiary of PT Tunas Ridean TBK which is engaged in the sale and service of Toyota vehicles. This research uses the HIRARC method. Making HIRARC is divided into 3 stages, namely identifying hazards, risk assessment and risk management. There are 8 work activities at PT Tunas Toyota Serang, of the 8 work activities have 31 potential work accidents that can occur. Of the 31 potential work accidents, 16 potential work accidents with low risk, 13 potential work accidents with medium or moderate risk, and 2 potential work accidents with high potential. Risk control in preventing work accidents can be done by using personal protective equipment, substitution, administrative control and engineering control.